Evaluasi Sistem Monitoring Antrian Menggunakan Framework COBIT 4.1 - Hidayat, Rahmat Rian (Universitas Komputer Indonesia, 2023)
Service is the main thing in the service sector. The hospital is one of the health services for the general public. Currently, the queue monitoring information system has been running, where patients can register through the system, but there are still obstacles, namely invalid patient data. From these problems, it is necessary to evaluate the queue monitoring information system using the COBIT framework. The COBIT framework used is version 4.1, focusing on the ME (Monitor and Evaluate) domain on the ME1 (Monitor and Evaluate IT) sub domain. This study uses qualitative methods with data collection techniques using interviews, questionnaires and analysis of the COBIT 4.1 evaluation framework. The results of this study are the maturity level of monitoring and evaluation of system performance (ME1) is still at level 2, which means that the condition where the hospital has had a pattern that is repeatedly carried out in managing activities related to information technology governance, but its existence has not been defined clearly. good and formal so that there are still inconsistencies. The recommendation is that agencies must have concern for monitoring data as well as standards, policies and procedures for monitoring IT performance so that later they can be organized according to business processes.